Odantapuri University: Reviving the Lost Legacy of Buddhist Scholarship in Ancient India - Sharma, Nikesh (Journal of Innovation in Education and Social Research, 2025)
Odantapuri University, established in the 8th century CE by Gopala I of the Pala dynasty, stands as one of the earliest and most distinguished centers of Buddhist learning in ancient India [1]. While often eclipsed in historical discourse by renowned institutions such as Nalanda, Vikramshila, and Takshashila, Odantapuri carved its own niche as a dynamic hub of scholastic excellence and cultural exchange [2]. The university attracted monks, scholars, and students from across Asia, fostering a vibrant intellectual environment where Buddhist philosophy flourished alongside studies in logic, linguistics, medicine, astronomy, and other sciences [3]. Its emphasis on Mahayana Buddhism and monastic discipline not only strengthened doctrinal traditions but also facilitated cross-cultural dialogues that shaped the broader Asian Buddhist world [4]. The architectural grandeur of Odantapuri, coupled with its rigorous academic curriculum, reflected the synthesis of spiritual practice and intellectual inquiry characteristic of the Pala era [5]. However, the university’s flourishing legacy faced a catastrophic end during the Islamic invasions of the 12th century, when it was destroyed, marking a profound loss to the heritage of Indian and world education [6]. This paper explores the historical foundations, academic and pedagogical structures, and cultural significance of Odantapuri University through a multidisciplinary lens, drawing upon historical chronicles, archaeological evidence, and comparative studies of contemporaneous institutions [7]. By re-examining its enduring contributions and tragic demise, the study seeks to rekindle scholarly engagement with Odantapuri, highlight its overlooked legacy in the history of education, and advocate for renewed research and preservation efforts to safeguard the remnants of this forgotten intellectual beacon [8].